Ultrafine‐grained β‐Sialon fabricated by two‐stage sintering and study on diffusion toughening of Ti–22Al–25Nb. Issue 3 (17th January 2023) - Xi, Chenyang; Cui, Tianlun; Guo, Haoshan; Liang, Kangbo; Zhang, Chunxiang; Luo, Junting
Abstract: The ultrafine‐grained β‐Sialon ceramics were fabricated by spark plasma sintering at different temperatures with inorganic Al2 O3 –Y2 O3 and Ti–22Al–25Nb intermetallic powder as composite additives. The research showed that β‐Sialon ceramics achieve two‐stage sintering densification. Al2 O3 –Y2 O3 inorganic additives promoted the synthesis and densification of β‐Sialon ceramics at 1125–1215°C. Ti–22Al–25Nb intermetallic powder diffused Ti and Nb elements at 1240–1425°C, thereby improving the fracture toughness of β‐Sialon ceramics. The maximum fracture toughness (∼9.69 MPa m 1/2 ) under 19.6 N was obtained for β‐Sialon ceramics sintered at 1600°C.